An Improved Total RNA Extraction Method for White Jelly Mushroom Tremella fuciformis Rich in Polysaccharides - Zhu, Hanyu (Mycobiology, 2017)
An improved method for extracting high quality and quantity RNA from a jelly mushroom and a dimorphic fungus—Tremella fuciformis which is especially rich in polysaccharides, is described. RNA was extracted from T. fuciformis mycelium M1332 and its parental monokaryotic yeast-like cells Y13 and Y32. The A260/280 and A260/230 ratios were both approximately 2, and the RNA integrity number was larger than 8.9. The yields of RNA were between 108 and 213 µg/g fresh wt. Downstream molecular applications including reverse transcriptional PCR and quantitative real-time PCR were also performed. This protocol is reliable and may be widely applicable for total RNA extraction from other jelly mushrooms or filamentous fungi rich in polysaccharides.